Microstructure and Electric Properties of CaCu3Ti4O12 Multilayer Capacitors. Issue 1 (30th September 2014) - Löhnert, Romy; Bartsch, Heike; Schmidt, Rainer; Capraro, Beate; Töpfer, Jörg; Feteira, A.
<x xml:space="preserve">Abstract</x> In a three‐step development process CaCu3Ti4O12‐based bulk ceramic pellets, tape‐casted multilayer ceramic laminates, and multilayer ceramic capacitors with cofired electrodes were fabricated. The sintering behavior, microstructure, electrical resistivity, and dielectric properties were studied. At a firing temperature of 1050°C, an effective permittivity of about ε′ = 60 000 and 10 000 was observed for sintered pellets and multilayer laminates, respectively. The typical grain growth observed in pellets is suppressed in multilayer laminates. Impedance spectroscopy was employed to show that the bulk grain resistivity is similar in pellets and multilayer laminates, but the grain‐boundary resistivity is higher in pellets. Tapes were processed into multilayer capacitors with Ag/Pd electrodes and cofired at 1050°C. All three types of samples, pellets, laminates, and capacitors were also processed with a glass additive, in which case they can be cofired at a lower temperature of 900°C. In glass‐containing pellets, the temperature dependence of permittivity is weak and exhibits X7R characteristics for frequencies below ≈ 60 kHz. Our results demonstrate the high potential of CaCu3Ti4O12 for application in monolithic as well as in integrated multilayer capacitors.